Inovasi Prosedur Pemutusan Hubungan Kerja di Lembaga Pendidikan Islam: Perspektif Hukum, Etika, dan Manajemen - Aini Mahfudhoh; Imam Junaris; Binti Maunah (JoIEM (Journal of Islamic Education Management), 2025)
Termination of employment in Islamic educational institutions is a strategic challenge that affects the sustainability of the institution and the welfare of educators. This study aims to develop an innovative model of sharia-based termination procedures that is fair, humane, and in accordance with national law and Islamic principles. This study used a systematic literature study method with qualitative analysis of 10 primary sources consisting of journal articles published in the last ten years. The analysisfocused on the causes of employment termination, implementation procedures, psychological impacts, and variations in practice in the field. The results revealed that termination was generally triggered by declining enrolment, organizational restructuring,performance issues and budget constraints. Although most institutions have implemented formal procedures such as writtennotification and severance pay, the implementation of deliberation and transparency still varies. The psychological impactsexperienced by educators include decreased motivation and a sense of injustice, potentially lowering the professionalism of theremaining staff. This research offers a model of sharia-based termination procedures that integrates open deliberation, theestablishment of a multi-stakeholder mediation board, digitization of management systems, as well as collaboration with Islamicfinancial institutions. This model is a new contribution that emphasizes fairness, ethics, and efficiency.